Global climate change and coastal resources and installations in Nigeria impacts and response measures - Tobor, John G.; Ibe, A. Chidi (Francisgraphix LTD, 1992)
Proceedings of the Natioanl Seminar on Global Climate Change and Coastal Resources and Installations : Impacts and response measures 20-21 November, 1990